IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH EXAMPLES NON EXAMPLES LEARNING MODEL IN LEARNING BAHASA INDONESIA AT SDN 011 PAUH ANGIT - Nurlela (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
A fundamental problem faced by fifth grade students at SDN 011 Pauh Angit was the low achievements in learning Bahasa Indonesia. As a result, the learning process became less effective at schools. The learning model applied in this research was example non example method, which was useful for making it easier for students to understand the concept of learning by looking directly at examples of the topic being taught. The purpose of this study was to improve the students’ achievement in learning Bahasa Indonesia at SDN 011 Pauh Angit. This research was a classroom action research which aimed to improve and enhance the learning process in the classroom. This study found that example non example learning model was effective to enhance the students’ learning outcomes. Based on the results of observations, there was an increase in teachers’ activities for 57% (sufficient category) in the first meeting. Moreover, in the second meeting, the activities increased for 71% which was in good category. Meanwhile, in the third meeting, he teachers’ activities increased for 83% with very good category, and in the fourth meeting, the percentage increased to 92% with very good category. In addition, data on students’ activities revealed that in the first meeting, the students’ activities increased for 59% with sufficient category, and it increased at the second meeting for 72% with good category. Then, at the third meeting the percentage reached 85% with very good category, and at the fourth meeting, it was 90% with the category of very good. Lastly, data on the improvement of students’ learning outcomes revealed that the score of daily test I was 78 and daily test II was 88.